Overactive bladder: a multicenter study in Pakistan - Sheikh, Masood Ahmed; Ahmed Fawad; Khalid Javed Rabbani; Syeda Batool Mazhar; Shahzad Ali; Haleema Yasmin; Salman EL khalid; Waqar Azim Niaz; Humma Quddusi; Muhammed Akhtar Anwer; et al. (Journal of the Pakistan Medical Association, 2022)
Objective: To determine the overall prevalence of overactive bladder in Pakistan, and to determine the difference in prevalence in relation to gender. Method: The multicenter study was conducted from February 2017 to October 2018 at 11 institutions across the country, and comprised randomly selected healthy subjects of either gender who were assessed on the basis of symptoms defined by the International Continence Society for overactive bladder. Data was collected using a questionnaire based on the symptoms which was filled for the respondent by designated health workers. Data was analysed using SPSS 23. Results: Of the 1291 respondents, 632(49%) were males with a mean age of 37.8+14.4 years, and 659(51%) were females with a mean age of 38.3+13.7 years. The overall prevalence of overactive bladder was 82(6.4%). Among the males, it was 15(2.4%) and among the females 67(10.2%) (p=0.001). Urgency, frequency and nocturia were reported by 82(6.4%) respondents; 15(1.2%) males and 67(5.2%) females (p=0.001). Conclusion: The prevalence of overactive bladder was found to be low when assessed with strict application of the three classical symptoms of the condition. Continuous...